Considere que a função:
Anexos:
![](https://pt-static.z-dn.net/files/d90/07f991dcc0a57042417abab7afa20009.png)
Soluções para a tarefa
Respondido por
0
Resposta:
f(3) + f(-3) temos 2-1 = 1
Explicação passo-a-passo:
√x+1 x ≥ 3 temos f(3) = √3+1 √4 = 2
x+1/2 x < 3 temos f( -3 )= -3+1/2 -2/2 =-1
f(3) + f(-3) temos 2-1 = 1
Perguntas interessantes
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Matemática,
9 meses atrás
Física,
11 meses atrás
Português,
11 meses atrás
História,
1 ano atrás
História,
1 ano atrás
Português,
1 ano atrás